Pengurangan Biaya Produksi Dengan Mengurangi Hari Kerja (Studi Kasus: PT. HDD Muka Kuning) - Qomarotun Nurlaila (Fakultas Teknik, Universitas Riau Kepulauan, 2020)
This research was conducted at PT. HDD, which is a Japanese PMA and is engaged in manufacturing HDD (Hard Disk Drive) components. On mid of August 2020, customer of PT. HDD revise the order quantity. Customer reduce order quantity from August to December 2020.With the phenomenon of decreasing orders, it is necessary to make efforts to reduce production costs. By reducing production costs, it is expected that the company will get profit. Reduction of production costs is carried out on labor costs and utility costs (water and electricity). To achieve this goal, management established 5 policies so that labor costs and utility costs (electricity and water) were reduced.The policies taken relate to eliminating / controlling overtime hours, stop contract employees and not recruit new employees, moving employees from the excess employee section to the understaffed section, reducing days work for 3 days (done in September 2020) and reduce work days by 2 days (done in October 2020).